Simulation of heterogeneosly catalysed esterification for biodiesel production using reactive distillation column - Chong, Kelvin Chee An (2009)
Biodiesel has become an attractive focus due to its environmental friendliness and benefits. Waste and non-edible raw materials have been employed for producing biodiesel in order to make it competitiveness with the petroleum-based diesel. Waste raw materials can contain substantial amount of free fatty acids (FFAs). Esterification reaction is one of the major routes to produce biodiesel from the raw material with high FFAs. However, the conventional process is facing several problems. Therefore, the development of an efficient continuous process for biodiesel manufacturing is required in which the use of a solid catalyst is highly desirable in order to suppress costly chemical processing steps and waste treatment. In the present study, an innovative esterification process of fatty acids based on reactive distillation was proposed for the biodiesel production. Process simulation was performed to study the feasibility of producing biodiesel using reactive distillation column, to identify the important operating and design factors (reactant ratio, reflux ratio, pressure, distillate-to-feed ratio, number of stages, and catalyst weight), and to propose a suitable configuration of the pilot plant for the biodiesel production. The esterification process was modelled by the esterification of oleic acid with methanol. The reaction was catalysed heterogeneously by sulfonic exchange acid resin. A pragmatic kinetic based on pseudohomogeneous model was incorporated into the reactive distillation model. From the simulation, it was found that it is feasible to produce biodiesel using reactive distillation column. The distillate-to-feed is best suited at 0.4 while the reflux ratio is best-suited in the range of 0.04 to 0.10. Pressure can be up to 3 bar. The changes in catalyst weight apparently contribute to the scale of production for biodiesel. The catalyst weight used is in the range of 250 to 500 gm. Finally, a suitable reactive distillation column configuration was proposed.-Author-